2022
DOI: 10.1532/hsf.4631
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Local and General Anesthesia for Transcatheter Aortic Valve Implantation: A Meta-Analysis and Systematic Review

Abstract: Background: This meta-analysis aimed to compare the potential effects of local anesthesia (LA) and general anesthesia (GA) for transcatheter aortic valve implantation (TAVI). Measurements: All relevant studies were searched from Pubmed, EMbase, Web of Science, and the Cochrane Library (January 1, 2016, to June 1, 2021). The main outcomes of this literature meta-analysis were 30-day mortality, procedural time, new pacemaker implantation, total stay in the hospital, use of the vasoactive drug, and intra-and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Furthermore, an apparently paradoxical finding in the current meta-analysis was the significant but weak evidence showing a shorter procedural time associated with the use of CS/MAC compared to GA. Similarly, two previous meta-analyses have also demonstrated a shorter procedural time with local anesthesia compared to GA ( 14 , 15 ). One possible explanation may be a coincidence between the learning curve of the TAVR procedure and the choice of anesthesia strategy.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Furthermore, an apparently paradoxical finding in the current meta-analysis was the significant but weak evidence showing a shorter procedural time associated with the use of CS/MAC compared to GA. Similarly, two previous meta-analyses have also demonstrated a shorter procedural time with local anesthesia compared to GA ( 14 , 15 ). One possible explanation may be a coincidence between the learning curve of the TAVR procedure and the choice of anesthesia strategy.…”
Section: Discussionmentioning
confidence: 52%
“…Results of prior studies regarding the influence of anesthetic approaches for TAVR on medical resource utilization remain inconsistent. Although a previous meta-analysis on 10,572 patients from 26 studies reported that the use of local anesthesia was associated with a shorter hospital LOS (i.e., 2.09 days) and ICU LOS (i.e., 0.18 days) ( 14 ), another recent meta-analysis of 17 studies involving 20,938 patients found no significant difference in the length of total hospital stay between patients receiving local anesthesia and those undergoing GA ( 15 ). Our results revealed a shorter ICU LOS (weak evidence) and hospital LOS (strong evidence) with the use of CS/MAC compared to GA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies [ 56 , 57 , 58 ] have found no significant difference in 30-day mortality between the above two anesthetic strategies for TAVI patients. A previous meta-analysis [ 59 ] pointed out that the anesthesia method did not influence the average 30-day mortality rate, which was 100/1532 patients in the LA group and 114/2061 patients in the GA-group [RR = 0.91, 95% CI (0.53, 1.56), p = 0.72].…”
Section: Discussionmentioning
confidence: 99%